Synthesis of Geopolymer from Coal Fly Ash and its Comparative Study with Fly Ash Based Ordinary Nepalese Cement - Gurung, Deepa Humbahadur; Jha, Vinay Kumar (Scientific World, 2020)
The world cement industry is responsible for 5-8 % of the total CO2 emission. Thus, the cement industry has a crucial role in global warming. The search for an alternative green inorganic binder with improved durability led to the discovery of alkali-activated binder termed “geopolymer”. In this study, geopolymer was synthesized from coal fly ash (CFA) with the parameters such as particle size ≤ 53 μm, NaOH concentration 8 M and the mass ratio of CFA/Na2SiO3 was 0.75. For the comparative study with fly ash based cement, the cement mortars were prepared by varying the cements and mass ratio. The highest compressive strength (14.16 MPa) of the cement mortar was however obtained with 1:3 cement sand ratio after 7 days of curing, the ratio of 1:4 was considered for comparison. The cement and geopolymer mixture mortars were also prepared with varying (cement + sand) and (CFA+ NaOH+ Na2SiO3) mass ratio. The maximum compressive strength of 3.84 MPa was obtained for 1:2 mass ratio with 7 days of curing. The maximum compressive strengths of CFA based geopolymer, CFA added cement and cement and geopolymer mixture were 17.06, 21.3 and 11.42 MPa with 90 days of curing respectively.